Brackish Tidal Marsh Management and the Ecology of a Declining Freshwater Turtle. - Agha, Mickey; Yackulic, Charles B.; Riley, Melissa K.; Peterson, Blair; Todd, Brian D. (Environmental Management, 2020)
Water management practices in tidal marshes of the San Francisco Bay Estuary, California are often aimed at increasing suitable habitat for threatened fish species and sport fishes. However, little is known about how best to manage habitat for other sensitive status species like the semiaquatic freshwater Western Pond Turtle (Actinemys marmorata) that is declining throughout much of its range. Here, we examined the basking activity, abundance, survival, and growth of Western Pond Turtles at two brackish water study sites in Suisun Marsh, California that differed in how they were managed, with one having passive management (i.e., no active water regulation) and another having active management (i.e., water regulated for seasonal hunting). Our results revealed that basking activity was greatest when salinity, water stage, and air temperatures were low, shortwave radiation was high, and wind levels were intermediate. These preferred habitat characteristics often reflected conditions that were naturally maintained at the passively managed, muted tidal site. We also found that turtles were more abundant and had higher survival rates in the passively managed habitat compared to the actively managed habitat (201–323 turtles/km2 and 96% survival versus 11–135 turtles/km2 and 77% survival, respectively). Finally, characteristic growth constants from von Bertalanffy models showed that turtles grew more quickly in passively managed habitat compared to the actively managed habitat. Our results suggest that management strategies for this sensitive status species may be more effective if they protect passively managed muted tidal systems that limit or delay extreme cycles of salinity and water levels and conserve elevated terrestrial buffer zones adjacent to muted and full tidal systems. Short Summary: Western Pond Turtle basking activity patterns and population dynamics are driven by various environmental factors, some of which are influenced by regional and local water management practices.